La pandemia e il paradigma immunitario: le sfide della politica tra sicurezza e solidarietà - Coco, Antonella (SocietàMutamentoPolitica, 2023)
Over a short period of time, countries around the world have been facing health and economic risks due to the spread of the Covid-19 pandemic. In this paper, we use the immune paradigm to interpret the impact and consequences of the pandemic on society, in social relations and especially at the political level, when democratic systems are called to face new challenges. They concern the contrast between protection and security, on the one hand, and securitarian impulses on the other, in order to guarantee fundamental democratic freedoms; the extension of immunity protection as equally as possible, by contrasting the inequalities which in various areas (from health to the economy) have emerged and increased during the pandemic; the capacity to simultaneously guarantee the need for immunization and the drive for solidarity; finally, the propensity for forms of cooperation between States as opposed to forms of national sovereignty in dealing with the risks that arise at a global level.